1998
DOI: 10.1099/00221287-144-7-1773
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen protection of nitrogen fixation in free-living Azorhizobium caulinodans: the role of cytochrome aa3

Abstract: ~~ _____The growth properties of Azorhizobium caulinodans wild-type and a cytochrome aa, mutant strain, both growing with N, as N source at fixed dissolved partial oxygen pressures in the range 0.5400 kPa, were studied by making use of continuous cultures (chemostats and pH-auxostats) and transient cultures. In succinate-limited chemostats, the wild-type exhibited a higher growth yield than the aa, mutant at every dissolved oxygen tension tested, indicating activity of cytochrome aa, in this entire oxygen regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…The adaptation includes expression of nif genes in microaeorbic conditions (Fischer, 1994), conformational protection of nitrogenase by FeSII protein (Moshiri et al , 1994; Ureta & Nordlund, 2002), respiratory protection (Bertsova et al , 2001), and so on (Dong et al , 2002). In A. caulinodans , it is reported that cytochrome aa 3 plays a role in protecting nitrogen fixation from O 2 (Boogerd et al , 1998). Duplication of nifH genes in A. caulinodans would also be related to the adaptation of nitrogen fixation to recent aerobic atmosphere.…”
Section: Discussionmentioning
confidence: 99%
“…The adaptation includes expression of nif genes in microaeorbic conditions (Fischer, 1994), conformational protection of nitrogenase by FeSII protein (Moshiri et al , 1994; Ureta & Nordlund, 2002), respiratory protection (Bertsova et al , 2001), and so on (Dong et al , 2002). In A. caulinodans , it is reported that cytochrome aa 3 plays a role in protecting nitrogen fixation from O 2 (Boogerd et al , 1998). Duplication of nifH genes in A. caulinodans would also be related to the adaptation of nitrogen fixation to recent aerobic atmosphere.…”
Section: Discussionmentioning
confidence: 99%
“…Investigations of cellular levels of SOD and catalase in A. vinelandii revealed that both enzymes increase when the prevailing O 2 concentration is raised [51]. Autoprotection as a possible mechanism of protection of nitrogenase has been discussed to occur not only in A. vinelandii and K. pneumoniae but also in Azorhizobium caulinodans and various members of the cyanobacteria [6,30,48,52].…”
Section: Alternative Strategies Of Protectionmentioning
confidence: 99%